Current two EGFR mutations in lung adenocarcinoma - case report - Svaton, M; Pesek, M; Chudacek, Z; Vosmiková, H (Klinicka onkologie, 2015)
Nowadays, EGFR TKIs (epidermal growth factor receptor-tyrosine kinase inhibitors) targeted therapy is well established treatment for patients with the so-called EGFR common mutations with advanced or metastatic nonsmall cell lung cancer. The efficacy for the so-called rare and especially for the very rare complex EGFR mutations is not clear. We describe a case of a 63- year-old female with metastatic nonsmall cell lung cancer with complex EGFR mutation (G719X + S768I) who had been treated by gefitinib. She achieved progression free survival within eight months. Then, we discuss our case with other literature case reports. Together, it seems that described complex EGFR mutation has a relatively good sensitivity for EGFR TKIs treatment.Key words: nonsmall cell lung cancer - EGFR gene - EGFR protein - complex mutations - rare EGFR mutations - EGFR TKIs.
Keywords: Adenocarcinoma; nádory plic; nemalobuněčný karcinom plic; adenokarcinom plic; Adenocarcinoma of Lung; Lung Neoplasms; Humans; Radiography; inhibitory proteinkinas; lidé středního věku; Carcinoma, Non-Small-Cell Lung; Quinazolines; ErbB Receptors; chinazoliny; radiografie; Female; lidé; Gefitinib; erbB receptory; Protein Kinase Inhibitors; ženské pohlaví; Middle Aged; gefitinib; adenokarcinom